Community Psychiatry in India Needs a Holistic Approach - Ranabir Pal; Swapan Kumar Paul; Gautam Sarker; Pandurang V Thatkar (Medsci Publications, 2016)
Citizens with neuro-psychiatric disorders fatigue their caregivers at both physical and mental levels. In absence of optimum social support systems, much of the caregiving role for the psychiatric disorders is left to the family members, often shouldered by the unaffected spouse, often a woman that happens behind our eyes. Health professionals, besides caring for the patient, need to explore with empathy to find capacity building in support of mechanism of skill building and relief for the caregivers among relations and relatives. Health care delivery systems in low and middle income countries, despite their fragilities need to address such emerging challenges in neuro-psychiatric care, and care delivery machinery will have to adopt as well as solve an array of these problems. Setting up of reasonably priced and comprehensive care for persons with mental ill-health remains a challenging task even in developed world and the situation is worse in low-income and middle-income countries. Priority should be given to models with comprehensive, cost-effective and sustainable care. Community Psychiatry need to be developed as a tailor-made individualized services to the mentally - ill individuals, where the erudite psychiatrists will guide and contribute not only to curative services but also provide comprehensive package of services including promotive and preventive aspects of mental health. While an extensive body of research is currently being developed, there are innumerable of unexplored openings for potential research that have impending strengths to supplement the knowledge base and provide critical information to the health care providers as well as stakeholders as clear clinical practice guidelines in the call of the day in India.